Successful anaesthetic management of a case of hypertrophic obstructive cardiomyopathy posted for elective caesarean section using epidural anaesthesia with 0.75% Ropivacaine - Anjali R Bhure; Ketaki S Marodkar (Wolters Kluwer Medknow Publications, 2011)
Hypertrophic obstructive cardiomyopathy (HOCM) is a complex cardiovascular disorder with autosomal dominant inheritance and an incidence of 0.1-0.5% in pregnant females. Anaesthetic management of a pregnant female with HOCM posted for elective caesarean section is a challenge, as even minor hemodynamic insults may lead to life-threatening complications. We report successful management of one such patient using epidural anaesthesia with 0.75% Ropivacaine.